Efektivitas Peacekeeping Operation Uni Afrika pada Konflik Darfur 2004 - 2007 - Arumsari, Gitra Fajar; Indriastuti, Suyani; Eriyanti, Linda Dwi (e-Sospol, 2015)
Abstract .African Union Peacekeeping Operation in Darfur conflict or more known as African Mission in Sudan (AMIS) is one of African Union’s efforts to resolve the conflict in Darfur. This mission aimed to stop the ongoing violence between the government of Sudan and rebellious groups in Darfur that had caused the deaths of thousands of civilians since 2003. The Darfur conflict was originated from a competition due to the lack of natural resources; however, over the years, conflict Darfur evolved into a conflict regarding equality between two major groups in Africa, that is, Africans and non-Africans. Darfur is a state under the regional organization of African Union, so the African Union felt to have the responsibility to intervene the conflict in Darfur. African Union’s decision to intervene the conflict was prompted by African Union’s article that stated that African Union has the right to intervene a member of the union if in the case of genocide, war or crimes against humanity. AMIS started its operation in July 2004 and consisted of about 150 military armies. However, through the years AMIS continuously experienced an increase in the number of military components and in 2007 AMIS had 7000 military personnel in Darfur. This study aims to analyze the effectiveness of AMIS in resolving the Darfur conflict. The research used deductive method